Political economy of Caribbean monetary and financial integration. - Farrell, Terrence W. (1991)
Discusses the various characteristics of monetary integration and of financial integration, and considers two approaches to monetary union. Looks briefly at some of the difficulties of implementation. Suggests that economic and monetary union implies some form of political union.